PENERAPAN PERATURAN BUPATI JOMBANG NOMOR 41 TAHUN 2019 PADA PROGRAM MUATAN LOKAL KEAGAMAAN: Studi Kasus di SDN Tugu Kepatihan 2 Jombang - Rozaqi, Muhammad Lutfi; Umam , Khoirul; Arini, Aida (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2022)
Abstract: This article examines the application of Jombang district head regulation number 41 of 2019 to the local religious content program. Religious local content is a compulsory charge subject at the elementary and junior high school level, which was promulgated in Jombang district regulation number 09 in 2016 with the hope of the realization of